2003
DOI: 10.1016/s0895-7061(03)01016-1
|View full text |Cite
|
Sign up to set email alerts
|

T594M variant of the epithelial sodium channel β-subunit gene and hypertension in individuals of African ancestry in South Africa

Abstract: These results do not support an important role for the T594M variant of the ENaC gene contributing to either the development or severity of hypertension in subjects of African ancestry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 13 publications
1
22
0
Order By: Relevance
“…While of potential interest, these results remain unconfirmed so far. For the SCNN1B gene a-comparably rare-T594M polymorphism located in the C terminus but unrelated to the crucial PPPXY motif has been identified that was more frequent in hypertensive (∼8% heterozygous carriers) than in normotensive (∼2%) blacks (Baker et al 1998), results that were not reproduced in another black cohort (Nkeh et al 2003;Hollier et al 2006). A similar approach for the SCNN1G subunit resulted in the identification of a promoter polymorphism (G-173A) and a silent polymorphism in exon 3 with allele frequencies of ∼25% each (Persu et al 1999;Iwai et al 2001).…”
Section: Liddle's Syndromementioning
confidence: 99%
“…While of potential interest, these results remain unconfirmed so far. For the SCNN1B gene a-comparably rare-T594M polymorphism located in the C terminus but unrelated to the crucial PPPXY motif has been identified that was more frequent in hypertensive (∼8% heterozygous carriers) than in normotensive (∼2%) blacks (Baker et al 1998), results that were not reproduced in another black cohort (Nkeh et al 2003;Hollier et al 2006). A similar approach for the SCNN1G subunit resulted in the identification of a promoter polymorphism (G-173A) and a silent polymorphism in exon 3 with allele frequencies of ∼25% each (Persu et al 1999;Iwai et al 2001).…”
Section: Liddle's Syndromementioning
confidence: 99%
“…In contrast, neither the rise in aldosterone [ϩ283Ϯ281 versus ϩ356Ϯ403 nmol/L (ϩ10.2Ϯ10.1 versus ϩ12.8Ϯ14.5 ng/dL); Pϭ1.0] nor the rise in renin (ϩ17.2Ϯ17.0 versus ϩ21.3Ϯ20.9 U/mL; Pϭ0. 6) were different between the T594M heterozygotes and control subjects, and hyperkalemia was not observed in any subjects.…”
Section: Response To Amiloride Treatment In T594m Heterozygotes and Cmentioning
confidence: 68%
“…4 However, the enthusiasm generated from these positive association studies 2,4,5 has been tempered by independent reports that failed to confirm such an association. 6,7 The conflicting data surrounding this allele might derive from inadequate sample size, sampling biases inherent in clinic populations, the variability in resting blood pressure (BP) over time, confounding effects of drug treatment, and the multiplicity of environmental exposures and signaling pathways involved in the regulation of resting BP.The BP responsiveness to certain drugs, which predominately target a single BP-regulating pathway, might link more directly with the genetic underpinnings of hypertension than resting BP alone. The potassium-sparing diuretic amiloride, a specific ENaC antagonist, is normally a weak antihypertensive agent but has been proposed as the ideal treatment for hypertension in blacks carrying the T594M allele.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Our patient is a South African black child who tested heterozygous for the βT594M mutation. The association of βT594M mutation and hypertension has been described mainly in studies of black adults from Ghana [8], South Africa [9], USA [10], and London [5]. On the contrary, Hollier et al did not find any association of hypertension and βT594M mutation in their study among black people in Texas and Jamaica [11].…”
Section: Discussionmentioning
confidence: 91%